A Pilot Study: The Impact of COVID-19 on Student Learning in an Academic Service-Learning Course - Simons, Lori; Blank, Nancy; Schoneman, Sarah (Advances in Social Sciences Research Journal, 2022)
This pilot study examined the impact from COVID-19 on academic learning. An explanatory mixed-methods research design was used to explore student learning outcomes for 70 students who participated in an academic service-learning course during the pandemic. Student surveys revealed increases in their racial-cultural-ethnic identity development and interest in multicultural work from the beginning to the end of the semester. Student reflections also indicate that they gained confidence and patience, reformulated diversity attitudes, and acquired White privilege awareness through participation in service activities with recipients who culturally differed from them. The impact of COVID-19 on student learning is discussed.